1644 Trainee Perspective in Sarcoma Care. (12th October 2021) - Leong, S; Clancy, R; Jessop, Z; Bragg, T
Abstract: Aim: Soft tissue sarcomas (STS) are rare and aggressive tumours. Appropriate multidisciplinary management requires robust knowledge of best practice and understanding of current guidelines. Plastic surgery trainees must therefore be proficient in the assessment, investigation, and treatment of patients with STS. We aimed to evaluate trainee education, confidence, and competence in managing patients with STS. Method: All plastic surgery trainees in Wales completed an online questionnaire and written assessment. This was designed by the lead for STS and TPD. Formal training, knowledge of national guidelines and excision margins for different types of STS and skin cancer was assessed using short answer questions. A five-point Likert scale was used to assess trainee confidence in STS and skin cancer management and follow-up. Volume and type of teaching in sarcoma and skin cancer was also quantified. Results: Trainees received less sarcoma training and were less confident in STS assessment and follow-up, in comparison to skin cancer. More senior trainees or those with formal sarcoma training were more confident in skin cancer management (mean confidence rating 4.4 vs 2.2) and performed better in the written assessment of excision margins (mean score 100% vs 61.45%) Conclusions: Trainees receive less training in sarcoma with a significant impact on their competence and confidence in sarcoma care. We believe this is consistent across the United Kingdom as evidenced by just two sarcoma webinars held during the COVID-19 pandemic. Formal national evaluation of sarcoma teaching should be carried out to inform ongoing efforts to improve educational resources on this important topic for trainees.